APLIKASI E-COMMERCE BERBASIS WEB MOBILE PADA INDUSTRI KONVEKSI SERAGAM DRUMBAND DI PEKON KLATEN GADINGREJO KABUPATEN PRINGSEWU - Fergiawan Listianto; Fauzi Fauzi; Rita Irviani; Kasmi Kasmi; Garaika Garaika (Jurnal TAM (Technology Acceptance Model), 2017)
Convection Drumband Uniform is a convection that makes and sells drumband uniforms in Klaten Gadingrejo Village. System sales, promotion and marketing still use manual system. For that we need a system that can help Convection Drumband Uniforms to be known to the wider community. With the design of Mobile Web-based E-commerce application is the PHP programming language, text editor Macro Dreamweaver, and Photoshop CS6. This app can ease promotion, sales, and expand marketing.